Determination of Suspects Based on Regulation of the Chief of the Indonesian National Police Number 6 of 2019 Concerning Criminal Investigation (Case Study Number: 10/Pid.Pra/2024/PN Bdg) - Robiatul Adawiyah; Nynda Fatmawati O (Journal of Law, Politic and Humanities, 2025)
This research aims to find out whether the arrangements for determining suspects in National Police Chief Regulation Number 6 of 2019 concerning Criminal Investigations are in accordance with the provisions in the Criminal Procedure Code (KUHAP). This research uses normative research methods with a prescriptive approach. The data used in this research is secondary data obtained from library materials, such as books, journals and statutory regulations. The results of the research show that "the beginning of evidence" in National Police Chief Regulation Number 6 of 2019 do have several differences with the provisions in the Criminal Procedure Code who have been perfected by the ruling of the constitutional court number 21 / puu-xii / 2014. that there must be 2 sufficient tools of evidence and the investigator's objective conviction to satisfy the establishment of a suspect. But, contrary to the regulations of the 6/2019 capture, there was an SPDP that contained the identity of the suspect. This would be a conflict of norms, but the stipulations of the 6/2019 capture should be consistent with the requirements of KUHAP.